Total and regional ASPECT score for non-contrast CT, CT angiography, and CT perfusion: inter-rater agreement and its association with the final infarction in acute ischemic stroke patients. (August 2022) - Chu, Yue; Ma, Gao; Xu, Xiao-Quan; Lu, Shan-Shan; Cao, Yue-Zhou; Shi, Hai-Bin; Liu, Sheng; Wu, Fei-Yun
Background: Alberta Stroke Program Early Computed Tomography Score (ASPECTS) is a grading system to assess the extent and distribution of early ischemic changes. Purpose: To assess inter-rater agreement for total and regional ASPECTS on non-contrast computed tomography (NCCT) images, CT angiography source images (CTA-SI), and CT-perfusion cerebral blood volume (CTP-CBV) maps, and their association with final infarction in patients with acute ischemic stroke (AIS). Material and Methods: A total of 96 consecutive patients with AIS who underwent pre-treatment NCCT and CTP were retrospectively enrolled. CTA-SI was reconstructed using the raw data of CTP. Total and regional ASPECTS were assessed on baseline NCCT, CTA-SI, and CTP-CBV, and on follow-up NCCT or diffusion-weighted imaging. Follow-up ASPECTS served as the reference standard for final infarction. Results: CTP-CBV demonstrated higher concordance for total ASPECTS (interclass correlation coefficient, 0.895 vs. 0.771 vs. 0.777) and regional ASPECTS in internal capsule, lentiform, caudate nuclei, M5 and M6, compared with NCCT and CTA-SI. CTP-CBV showed a trend of stronger correlation with final ASPECTS than NCCT and CTA-SI (0.717 vs. 0.711 vs. 0.565; P  > 0.05). ASPECTS in the internal capsule (ρ, 0.756 vs. 0.556; P  = 0.016) and caudate nucleus (ρ, 0.717 vs. 0.476; P  = 0.010) on CTP-CBV were more strongly correlated with follow-up ASPECTS than NCCT. CTP-CBV showed higher accuracy for predicting final infarction in the internal capsule (92.5% vs. 90.3% and 87.1%; P  > 1.000, P  = 0.125, respectively) and caudate nucleus (87.1% vs. 79.6% and 77.4%; P  = 0.453, P  = 0.039, respectively) than CTA-SI and NCCT. Conclusion: CTP-CBV ASPECTS might be more reliable for delineating early ischemic changes and predicting final infarction.